Penyelesaian Sengketa Merk Dagang Di Era Digital Dalam Perspektif Hukum Perdata: Penyelesaian Sengketa Merk Dagang Di Era Digital Dalam Perspektif Hukum Perdata - Mohamad Tohari; Loso; Irfan Rizky Hutomo (Faculty of Law, Universitas Pekalongan, 2025)
The use of a brand when in a trading activity is often classified as unfair competition, in an attempt to gain an advantage by taking advantage of someone else's brand, either by falsifying it in its entirety or only in certain parts, in other words, equality at its core. Many consumers are deceived when buying branded products because of plagiarism in the logo design or product packaging that has been known by the public and is very similar to the original form. There are still many business actors who are dishonest and violate the law. There are business actors who still plagiarize famous brands so that the products they make attract many fans. Therefore, there is a need for healthy competition in trade, so that no party feels disadvantaged in the process of trade, this study adopts the normative juridical method with a legislative approach and conceptual approach. The results showed that disputes related to the sale of counterfeit trademarks can be resolved both through court and out-of-court channels. The actions of sellers of counterfeit goods who trade products without the permission of the brand owner are certainly detrimental to the owner of the brand. In the face of brand infringement disputes, a wise step that brand owners can take is to resolve the issue out of court through mediation. This approach is expected to prevent further losses, especially for brand owners, while maintaining their reputation in the public eye regarding plagiarism issues. However, if mediation does not reach an agreement, the brand owner has the option of filing a lawsuit in the Commercial Court